Incidence of Early Marriage Induced Girl Dropouts at Secondary Level: A Study of Bharsho Village in Naogaon District - Ety Rani; Wardatul Akmam (CV. Literasi Indonesia, 2022)
In this study, efforts have been made to explore the incidence of early marriage-induced dropout among girls at the secondary level of education. This study has three objectives. There are: to find different factors that affected girls’ dropout; to investigate the extent to which child marriage functioned as a reason for girls’ dropout; To relate the findings of the study to Maslow’s theory of hierarchy of needs. Social survey and case study methods have been applied for data collection. Data have been collected from 131 respondents with informed consent. The research area of this study was Bharsho village under the district of Naogaon in Bangladesh. In this study, the socio-economic condition of respondents’ parents and father-in-law was poor. A majority of the respondents’ main reason for dropping out was early marriage. Early marriage was a very significant factor that affects girls’ dropouts. This study shows a strong relationship between Maslow’s hierarchy of needs, early marriage, and girls’ dropout.